Analisis Fenologi Tanaman dan Fase Pertumbuhan Sorgum (Sorghum Bicolor L. Moench) Lokal Sumba Timur - Jeni, Theresia; Kurnia, Theresa Dwi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aimed to obtain data on phenology and growth phases in sorghum genotype watar hammu miting tadda which is a local sorghum of East Sumba. The research used a qualitative descriptive method. Observations of the growth phase of sorghum plants follow the growth scale (growth stage). Observations of the phenology of sorghum plants consisted of leaf angle, stem diameter, leaf color, leaf width, chlorophyll count, leaf edge, leaf surface, leaf length, sugar content, seed description, growth phase, 1000 grain weight. This research was conducted in Wates Village, Getasan Subdistrict, precisely in the STP (Science Techno Park) Experimental Garden, which is located at an altitude of 1,050 meters above sea level with an average temperature between 15.5 and 30Â°C. The area of Wates Village is categorized as highland. The results of research on the growth phase showed that seed germination occurred at 4 days after planting (HST). The maximum vegetative phase starts at 30-32 days after germination. And the generative phase which is indicated by the beginning of the release of flower panicles is around 67-74 hst. Thus, it can be concluded that the sorghum genotype watar hammu miting tadda planted in the highland region shows good adaptation and has the potential to be developed.